Analysis of Human Resources Development Factors on Nurse Performance at Patient Ward, Dr. Abdoer Rahem Hospital, Situbondo, East Java - Setyanto, Agung; Suprapto, Sentot Imam; Dewi, Prima (Journal of Health Policy and Management, 2023)
Background: Hospitals are required to be able to provide optimal health services for the community by improving the performance of hospital employees, one of whom is a nurse. Important Human Resource development factors are education, training, work periods, transfers and promotions. These factors are expected to improve the performance of nurses in providing nursing services.The aims of this study was to describe the influence of Human Resource Development on the Nurse Performance.Subjects and Method: This was an analytic observational study carried out at dr. Abdoer Rahem Hospital, Situbondo, East Java, from 12 to 28 May 2022. A sample of 112 nurses was selected by simple random sampling. The dependent variable was nursing performance. The independent variable are education, tenure, training, transfer, and promotion. The data were analyzed by a multiple linear regression.Results: Education (b= 2.23; 95% CI= 0.26 to 6.14; p<0.001), tenure (b= 0.19; 95% CI= 0.32 to 3.70; p<0.001), had trained (b= 0.08; 95% CI= 0.15 to 2.06; p= 0.042), transfer (b= 0.37; 95% CI= 0.16 to 2.36; p= 0.020), and promotion (b= 0.36; 95% CI= 0.15 to 2.22; p= 0.029) were significantly associated with nurse performance.Conclusion: There is a very significant influence between of education, work periods, training, mutation and promotion on the performance of nurses at dr. Abdoer Rahem Hospital Situbondo.Keywords: human resources development, nurse performanceCorrespondence: Agung Setyanto. Masters Program in Public Health, Strada Indonesian Institute of Health Sciences. Krajan Sumberejo, Banyuputih, Situbondo, East Java 68374, Indonesia. Email: agungwidiyana86@gmail.com. Mobile: +6281252468273.Journal of Health Policy and Management (2023)https://doi.org/10.26911/thejhpm.2023.08.01.05